Novel Approaches and Challenges of Discovery of Exosite Modulators of a Disintegrin and Metalloprotease 10 - Minond, Dmitriy (Frontiers in Molecular Biosciences, 2020)
A Disintegrin And Metaproteinase 10 is an important target for multiple therapeutic areas, however, despite drug discovery efforts by both industry and academia no compounds have reached the clinic so far. The lack of enzyme and substrate selectivity of developmental drugs is believed to be a main obstacle to the success. In this review, we will focus on novel approaches and associated challenges in discovery of ADAM10 selective inhibitors that can overcome shortcomings of previous generations of compounds and be translated into the clinic.